Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1259/dmfr/32524441
|View full text |Cite
|
Sign up to set email alerts
|

Congenital angiomyoma of the tongue: case report

et al.

Abstract: Angiomyomas of the oral cavity are rare benign vascular neoplasms. In particular, the congenital form has not been reported before in the English language literature. We present a congenital angiomyoma of the tongue that was found on the posterior middle of the tongue in an infant. On MRI, the mass showed an isointense signal to muscle on the T 1 weighted image and a slightly hyperintense signal on the T 2 weighted image. Immunohistochemically, tumour cells were positive to desmin and smooth muscle actin, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Most of the AL are diagnosed between the fourth and sixth decade of life [ 38 , 39 ], even if several studies have documented the tumor occurrence in subjects from 1 month to 84 years old [ 9 ]. There is only one study that reported a congenital tumor [ 21 ]. When AL occurs in this population, it is called leiomyomatous epulis, which clinically mimics a congenital granular cell tumor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the AL are diagnosed between the fourth and sixth decade of life [ 38 , 39 ], even if several studies have documented the tumor occurrence in subjects from 1 month to 84 years old [ 9 ]. There is only one study that reported a congenital tumor [ 21 ]. When AL occurs in this population, it is called leiomyomatous epulis, which clinically mimics a congenital granular cell tumor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present cohort was significantly younger than those investigated in other studies, with a mean age of 42.5 years at diagnosis and a peak in presentation in the fourth to sixth decades. Angioleiomyomas are particularly rare in children ( 1 , 3 , 11 – 14 ) and there is only one study of a congenital tumor ( 15 ). In the present study, the youngest patient was 10 years old, with an angioleiomyoma located in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…It is sometimes difficult to differentiate an angioleiomyoma from other spindle-cell tumors. Several oral tumors should be included in the histopathological differential diagnosis (16) , namely schwannomas, neurofibromas, fibromatoses, hemangiopericytomas, hemangioendotheliomas, well-diferentiated leiomyosarcomas, fibrosarcomas, inflammatory myofibroblastic tumors, and malignant schwannomas (11) . To that end, immunohistochemistry is a valuable, precise, and reliable method for establishing a definitive diagnosis (14,15) .…”
Section: Discussionmentioning
confidence: 99%